AUDIT OF ATTENDANCE INFORMATION SYSTEM AT MOTORCYCLE FACTORY USING COBIT 5 - Francka Sakti Lee; Johanes Fernandes Andry; Kevin Christianto; Honni Honni; Monica Clara (Universitas Teknokrat Indonesia, 2023)
The change in the fingerprint attendance system into an attendance application is called